Monitoring Pergeseran Tanah Tapak Tower Transmisi PT (PLN) Persero Dengan Menggunakan SMS Sebagai Notifikasi Peringatan - M. Diono; Yanda Pranapis; Khabzli, Wahyuni (Politeknik Caltex Riau, 2023)
Landslides are one of the causes of the collapse of the transmission tower of PT PLN (Persero) which caused power outages, therefore monitoring the shifting of the transmission tower tread is very necessary so that power outages due to the collapsed tower can be anticipated faster. In this study the authors made a study to monitor tower shifts by using Ultrasonic sensors and LVDT sensors (Linear Variable Differential Transducer), Ultrasonic sensors function to detect shifts from towers and LVDT sensors function to detect shifts from the left and right tread tower ground. In this research, there are three main sensors, namely 2 LVDT sensors and one Ultasonic sensor - each sensor is placed in a safe position from interference and has the least possibility of being affected by landslides, Ultrasonic sensors read the tower shift towards the sensor mounted on the center side and LVDT sensors read the shift ground tread tower on the left and right side of the tower. The sensor sends the signal then is converted by the ATMega 8535 microcontroller into a millimeter unit for LVDT sensors and centimeter meter for Ultrasonic sensors. To find out the changes that occur in the tower and tower ground. Every change in distance or the occurrence of a microcontroller shift sends event data in the form of tower numbers and tower shift distances from each sensor reading using SMS (Short Message Service) communication. The installed LVDT sensor has a reading accuracy rate of 98,05% for LVDT 1 and 98,98% for LVDT 2 in millimeters and an Ultrasonic sensor has a reading accuracy rate of 99,44% in centimeters.